Evolution of cellular HIV DNA levels in virologically suppressed patients switching to dolutegravir/lamivudine versus maintaining a triple regimen: a prospective, longitudinal, matched, controlled study. (26th February 2020) - Lombardi, Francesca; Belmonti, Simone; Borghetti, Alberto; Fabbiani, Massimiliano; Marchetti, Simona; Tamburrini, Enrica; Cauda, Roberto; di Giambenedetto, Simona
Abstract: Objectives: To assess the impact of switching to dolutegravir plus lamivudine maintenance therapy on the HIV cellular reservoir size. Patients and methods: This was a prospective, longitudinal, matched, controlled study. We enrolled virologically suppressed patients on stable three-drug ART who switched at baseline (BL) to dolutegravir/lamivudine (DT group) or maintained triple therapy (TT group); subjects in the TT group were matched 1:1 with those in the DT group according to age, gender, years since HIV diagnosis, years on ART and anchor drug. Total blood-associated HIV DNA levels were assessed by droplet digital PCR at BL and after 48 weeks (T48). Results were expressed as log10  HIV DNA copies/10 6 leucocytes. Results: We enrolled 40 patients in the DT group and 40 in the TT group; the two groups were homogeneous for all main characteristics except nadir CD4 cell count. At BL, HIV DNA levels were comparable between the DT and TT groups: 2.27 (IQR 1.97–2.47) and 2.26 (IQR 2.05–2.61) log10  HIV DNA copies/10 6 leucocytes, respectively. Change in HIV DNA load from BL to T48 was −0.105 (IQR −0.384 to 0.121, P  =   0.041) in the DT group and −0.132 (IQR −0.362 to 0.046, P  =   0.005) in the TT group, with a comparable decline observed between the two groups ( P  =   0.821). A higher HIV DNA decline was associated with higher BL CD4/CD8 ratio. Conclusions: Maintenance therapy with dolutegravir/lamivudine had the same impact as the triple regimen on HIV DNA levels after 48 weeks of treatment. These data seem to support the effectiveness of a dolutegravir/lamivudine dual regimen in controlling the magnitude of the cellular reservoir (www.clinicaltrials.gov, number NCT02836782).